2022
DOI: 10.1177/07482337221089585
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity associated with oxidative stress and inflammasome gene expression induced by allethrin in SH-SY5Y cells

Abstract: Pyrethroids, including allethrin, have largely been used as commercial insecticides. The toxicity of allethrin is little known, but it is assumed that, as occurs with other pyrethroids, it could cause alterations of the nervous system and pose both occupational and non-occupational health hazards. To evaluate the neurotoxicity of allethrin we used the MTT assay of SH-SY5Y neuroblastoma cells to determine cell viability. Dose-dependent reductions of cell viability served to compare the vehicle-group and the IC5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…After administering t-BOOH to both cell cultures, NO levels increased significantly. This similar effect of increasing NO in cell cultures by cytotoxic substances has been previously reported [ 32 , 43 ]. The NO concentrations were reduced in a dose-dependent manner by the effect of D. tortuosum from 50 µg/mL in both co- and pre-treatment in EA.hy926 cells, and from 100 µg/mL in co- and pre-treatment in SH-SY5Y cells.…”
Section: Discussionsupporting
confidence: 87%
“…After administering t-BOOH to both cell cultures, NO levels increased significantly. This similar effect of increasing NO in cell cultures by cytotoxic substances has been previously reported [ 32 , 43 ]. The NO concentrations were reduced in a dose-dependent manner by the effect of D. tortuosum from 50 µg/mL in both co- and pre-treatment in EA.hy926 cells, and from 100 µg/mL in co- and pre-treatment in SH-SY5Y cells.…”
Section: Discussionsupporting
confidence: 87%
“…Several studies have shown that various pesticides are capable of elevating levels of inflammatory factors, leading to neuroinflammation and impaired neuronal activity [ 50 ]. When the nervous system is exposed to pesticides [ 14 , 15 , 51 , 52 ], some nerve cells undergo activation of the NLRP3 inflammasome [ 53 ], including simultaneous activation of NFκB and other pathways, leading to the production and secretion of a large number of inflammatory factors such as IL1β, IL6, and TNFα, among others [ 54 , 55 ]; this increases mitochondrial dysfunction, with a consequent generation of ROS, MDA, and NO and a decrease in GSH and antioxidant enzymes such as CAT, SOD, and GPx [ 14 , 15 , 52 ], as we have reported in this study. Likewise, NRF2 (master of antioxidant regulation), which is activated by oxidative molecules such as ROS or by neurotransmission, needs to dissociate from the cytosolic protein KEAP1, so NRF2 enters the cell nucleus, resulting in the expression of several genes regulating antioxidant activity, including GPx, SOD, and others [ 21 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The MTT assay was used to observe whether the mitochondria of viable cells are able to reduce the tetrazolium-MTT reagent to formazan [ 15 ]. Briefly, after ipconazole treatments, 0.5 mg/mL MTT was added as a final concentration to each well and incubated for 2 h at 37 °C and 5% CO 2 , this time allowing metabolically active SH-SY5Y cells to reduce tetrazolium-MTT (yellow color) to a formazan salt (purple color).…”
Section: Methodsmentioning
confidence: 99%
“…Other studies found high ROS production in the liver and kidney tissue of rats exposed to triazoles [16,17]. In addition, ROS can induce cellular responses such as the activation of the inflammasome complex [18] or apoptosis [19]. The inflammasome is a cytosolic protein complex that, when activated, can induce a strong inflammatory response, triggering the release of proinflammatory cytokines interleukin 1β and interleukin 18 (IL-18) and even inducing cell death [20].…”
Section: Reagentsmentioning
confidence: 99%